A Two-Stage Spark Gap for Blumlein-Driven Transversely Excited Atmospheric Nitrogen Laser - Kau, WeeFong; Tou, TeckYong; Siew, WeeOng; Yap, SeongShan; Yang, RenBing; Chin, OiHoong (2004)
A two-stage spark gap is used to implement a two-stage Blumlein circuit for the efficient operation of a transversely excited atmospheric nitrogen laser. This enables a more compact circuit arrangement which employs an array of doorknob capacitors as the dummy capacitors instead of large parallel-plate capacitors but maintains a comparable laser output performance.